(untitled) (Doctor Virtualis, 2013)
Il contributo sostiene che una versione lunga e composita del Viaggio notturno del profeta e della sua ascensione, attribuita a Ibn ‘Abbas attraverso una figura più tarda conosciuta come al-Bakri, è diventata molto popolare e largamente diffusa nel tredicesimo secolo. Qui si propone una traduzione del viaggio celeste di Muhammad (la visita al paradiso) a partire da un importante manoscritto inedito di Istanbul copiato nella penisola araba verso la fine del tredicesimo secolo. Questa traduzione si propone come strumento per gli studiosi interessati alla tradizione islamica delle ascensioni celesti e per chi si occupa delle possibile influenze musulmane sull’opera di Dante. Nonostante non si dimostri che Dante avesse avuto accesso diretto a questa fonte nel momento in cui componeva la divina commedia, ci sono prove sufficienti che le versioni di questo racconto fossero diffuse in diverse parti del Mediterraneo, prima e durante la vita di Dante. L’autore fa propria la recente ipotesi interpretativa di Bencheikh che sottolinea il ruolo fondamentale della versione di Bakri del Mi’râj per la composizione dell’ormai noto Libro della Scala, tradotto in latino e lingua francese antico in al-Andalus nella seconda metà del tredicesimo secolo. This article argues that a long and composite version of the narrative of Muhammad’s night journey and ascension, one often ascribed to Ibn ’Abbas via a later figure known as al-Bakri, became especially popular and widely distributed in the thirteenth-century CE. It offers a translation of the Tour of Paradise section from a particularly important unpublished Istanbul manuscript preserving this version, copied in the Arabian peninsula near the end of the thirteenth-century. This translation could serve as a resource to scholars who are interested in the history of Islamic ascension narratives, and interested in the question of possible Muslim influences on Dante’s Divine Comedy. While the author of this article does not argue that Dante must have been aware of this particular manuscript as he composed his masterwork, he claims that there is enough evidence to suggest that versions of this narrative circulated in different parts of the Mediterranean before and during Dante’s lifetime. He supports the earlier conjecture by Bencheikh that the Bakri versions were likely foundational to the composition of the now famous "Book of Muhammad’s Ladder" that was translated into Latin and Old French in al-Andalus / Spain in the second half of the thirteenth-century.